Double Estrangement: Nasserism and Stagnation in Nihād Sharīf's The Conqueror of Time. Issue 1 (April 2019) - Campbell, Ian
Abstract : This paper examines Egyptian novelist Sharīf's 1972 canonical work of early Arabic sf Qāhir al-Zaman ["The Conqueror of Time"] from the perspective of double estrangement . The novel presents an inventor of cryogenics whose megalomania leads first to utopian visions of a future led by Egypt, then to his downfall. This estranges directly the rule of Gamal Abdel Nasser while retaining sufficient distance from more direct and therefore riskier critique. The text's focus on the history of Egyptian science also estranges Egypt's lack of scientific and technical progress in the twentieth century: dominance by a charismatic strongman renders recovery of the scientific glory of the distant past only possible in utopian visions.